Fuscoporia nebularis, (Hymenochaetaceae) a new endemic and threatened species from the cloud forests of southern Brazil - Comin, Marcel; Alves-Silva, Genivaldo; Salvador-Montoya, Carlos A.; Góes-Neto, Aristóteles; Drechsler-Santos, Elisandro Ricardo (Phytotaxa, 2024)
A new and threatened species of Fuscoporia from the cloud forests of southern Brazil is described. This species, associated with hardwood species of Myrtaceae, differs from other Fuscoporia species by having broadly ellipsoid basidiospores (2.9–3.8 × 2.3–3.1 µm) and hymenial setae that occasionally have a bifurcate and curved apex. Additionally, molecular analysis based on ITS and nrLSU sequences supports the new species. The conservation status of this new species of Fuscoporia is assessed as ‘Endangered’ based on IUCN criteria. We present the new species with illustrated morphological description, phylogenetic analyses and comparison with morphologically similar or related species. A key to the neotropical species of Fuscoporia is provided.